EVALUASI PENERAPAN SISTEM KARTU OBAT RAWAT INAP PADA ONE DAY DOSE DISPENSING TERHADAP POLA PENGGUNAAN OBAT DAN BIAYA OBAT PASIEN HIPERTENSI DI RSUD LIWA - , ERNA YANTI; , Dr. Erna Kristin, M.Si. Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: RSUD Liwa has implemented inpatient drug card system based on regulation of director number: 46/Kep/0499 on April 8, 1999 regarding the application of technical guidelines for one unit dose dispensing (OUDD) / one-day dose dispensing (ODDD) drug services for Askes patients, to improve the quality of the drug in terms of drug use and a decrease in the cost of inpatient medicine. Thus the pharmacy should be able to carry out the management of the drug is safe, efficient and patient-oriented. Evaluation of inpatient drug card system on indispensable management and quality improvement in health care. Methods: This research is a quasi experimental pretest-posttest design by comparing before and after application of the drug card ODDD, interventions performed by Hospital Pharmacy, as well as a retrospective data.The population in this study were all prescription / drug card inpatient hypertensive patients which entered Hospital Pharmacy, the drug use record from Internal medical room in 2012 and drug use list of of various types of financing in the hospital Pharmacy. Results: Evaluation results with the drug use after the implementation of inpatient drug card system showed percentage of drugs prescribed by generic name increased by 9,39%, percentage of drugs prescribed by branded name decreased 9,39%, percentage of drugs prescribed from essential drugs list were increased 8,75%, percentage of drugs prescribed from non essential drugs list were decreased 8,73%, the average number of drugs percounter declined 0,4, whereas drug use increased by 0,6%, average cost and total cost of antihypertensive drugs decreased Rp 4.939,4 and Rp 1.120.249, the average cost of non-antihypertensive drug and decreased total cost of Rp 3.160.7 and Rp 1.235.079 and the average drug cost per patient decreased after application of Rp78.510 inpatient drug card system on ODDD. Conclusion: After application of inpatient drug card system on ODDD drug use increased and decreased drug costs, as well as the most influential factor is the decrease in the cost of substitution of generic drugs, active supporting factors and other interventions in the form of regulations drugs prescribing by generic name. Keywords: Evaluation, inpatient drug card on ODDD, drug use, cost of generic name, cost of branded name, essential drugs list,non-essential drugs list, antihypertensives, non-antihypertensive